Experimental characterization of microcomposite magnetorheological elastomer - Rouabah, Salah; Aguib, Salah; Hadji, Mohamed; Kobzili, Lallia (Manufacturing Technology Journal, 2021)
This work presents an analysis experimental of dynamic properties of microcomposite magnetorheological elastomer (MMRE) by a dynamic mechanical analyzer (DMA). The charge of magnetized iron particles is 40% of the total volume. A dynamic mechanical analysis DMA was carried out, in the scanning mode of the amplitude of shear strain, and for magnetic field densities varying from 0mT to 325mT. The storage modulus G' and the loss modulus G'', of the elastomer decrease, when the amplitude of the strain increases. This trend is more pronounced under a higher magnetic flux density (250mT and 325mT). In the presence of the magnetic field, the level of these two dynamic moduli and of the damping increases considerably, passing from one value to another of the applied external magnetic field. As a result, the MR effect of MRE elastomers has increased significantly with increasing magnetic flux density.
Keywords: Microcomposite; Magnetorheological elastomers; Magnetic flux density; Dynamic mechanical properties; Iron particles.